2012
DOI: 10.1523/jneurosci.2783-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Mediated Facilitation of AMPA Receptor Function in the Dorsomedial Striatum: Implications for Alcohol Drinking Behavior

Abstract: We previously found that acute ex vivo as well as repeated cycles of in vivo ethanol exposure and withdrawal, including excessive voluntary consumption of ethanol, produces a long-lasting increase in the activity of NR2B-containing NMDA receptors (NMDARs) in the dorsomedial striatum (DMS) of rats (Wang et al., 2010a). Activation of NMDARs is required for the induction of long-term potentiation (LTP) of AMPA receptor (AMPAR)-mediated synaptic response. We therefore examined whether the ethanol-mediated upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 56 publications
(106 reference statements)
11
101
0
Order By: Relevance
“…C2cd2l was negatively correlated with 12 datasets for alcohol consumption and preference in male and female BXD RI strains across a range of alcohol concentrations (3-15%, v/v). Because of the relationship between C2CD2L and drinking in monkeys and mice, we then exploited the DBA/2J sequence (Keane et al, 2011;Wang et al, 2016) to extract all sequence variants in and around C2cd2l (e.g., rs32609282). While there are no high-impact C2cd2l variants , C2cd2l is associated with cis-acting expres- Figure 5.…”
Section: Identification and Validation Of Heavy-drinking Synaptic Biomentioning
confidence: 99%
See 2 more Smart Citations
“…C2cd2l was negatively correlated with 12 datasets for alcohol consumption and preference in male and female BXD RI strains across a range of alcohol concentrations (3-15%, v/v). Because of the relationship between C2CD2L and drinking in monkeys and mice, we then exploited the DBA/2J sequence (Keane et al, 2011;Wang et al, 2016) to extract all sequence variants in and around C2cd2l (e.g., rs32609282). While there are no high-impact C2cd2l variants , C2cd2l is associated with cis-acting expres- Figure 5.…”
Section: Identification and Validation Of Heavy-drinking Synaptic Biomentioning
confidence: 99%
“…Loss-offunction PRRT2 mutations are a causative factor for familial paroxysmal kinesigenic dyskinesia (PKD; Heron and Dibbens, 2013) and PKD patients with an insertion mutation in PRRT2 show enhanced spontaneous low-frequency fluctuations in corticostriatal circuitry (Luo et al, 2013). Neuroimaging studies in alcoholic individuals reveal aberrant executive control network activity and altered brain connectivity (Müller-Oehring et al, 2015;Zhu et al, 2015) that could reflect disruptions in GPM6A/ PRRT2 expression or function. Future studies are needed to validate the importance of these proteins in mediating the altered cognition, glutamatergic signaling, and corticostriatal circuitry observed in individuals with AUD.…”
Section: Novel Alcohol-sensitive Synaptic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least in the case of chronic alcohol and the DS, deficient LTD may also be coupled with changes in other forms of striatal plasticity, including N-methyl-D-aspartate (NMDAR)-mediated LTP (35). Previous studies have found that chronic EtOH up-regulates NMDAR function and plasticity in the DS (albeit medially), in a manner that underlies dependence drinking (20,21,36). Moreover, various forms of learning, including some of the tasks used in the current study, are critically dependent upon DS NMDARs (37,38).…”
Section: Significancementioning
confidence: 99%
“…Furthermore, activation of NMDAR is required for the induction of AMPA receptor (AMPAR)-mediated LTP (Malenka, 2003); we observed forward trafficking of AMPAR subunits to synaptic membranes and enhanced LTP as a consequence of alcohol-mediated increases of GluN2B activity in the DMS . Importantly, pharmacological inhibition of Fyn, GluN2B, or AMPARs in the DMS of rats or knockdown of PTPα in the mouse or rat DMS significantly reduced alcohol intake but did not affect the intake of rewarding substances Wang, Lanfranco, et al, 2010;Wang et al, 2012) and alcohol seeking in a reinstatement paradigm (Wang, Lanfranco, et al, 2010), or sucrose intake Wang, Lanfranco, et al, 2010;Wang et al, 2012). Interestingly, it lowered excessive alcohol drinking.…”
Section: Maladaptive Plasticity Learning and Memorymentioning
confidence: 97%